Education in A Pandemic Era: Access and Paradigm Transformation - Adison Adrianus Sihombing; Dian Nuri Ningtyas (Indonesia Social Justice Network (ISJN), 2022)
One of the major problems faced by countries around the globe during this pandemic is providing high-quality education services that can be accessed by all students. This learning difficulty that has become a symptom in various parts of the world has been seen only as a matter of ownership and mastery of technology. This understanding is incorrect and wrong in understanding reality. This has an impact on the formulation of action plans for solving problems during a pandemic. This paper aims to show the side of the challenge that can be interpreted as an opportunity. Distance learning during the COVID-19 pandemic is an essential shift in educational traditions. The data in this research was obtained from online surveys and in-depth interviews that involving students and teachers from various regions in Indonesia. Data from surveys and in-depth interviews were analyzed through the restatement, description, and interpretation stages. The results showed that learning difficulties were caused more by a lack of understanding of the essence of technology-based learning. This has an impact on the difficulty of changing the mindset, and perspective of the current learning reality. Most people still depend on and consider the traditional face-to-face learning method in the classroom as the only best strategy in the educational process compared to online systems. In other words, the existence of an educational paradigm transformation that aims to create student independence in education is still difficult to accept as a necessity. With this understanding, not only the reality of the pandemic can be understood more contextually, but also problem-solving efforts can be formulated with the right target. This paper suggests the need for further research to accommodate a larger sample and involving more representative informants to enable comparative analysis.